Relationship between background characteristics and residential satisfaction of young households in unplanned neighbourhoods in Kano, Nigeria - Abdu, Ado; Hashim, Ahmad Hariza; Abu Samah, Asnarulkhadi; Syed Salim, Azizah Salim (International Organization of Scientific Research, 2014)
This study examined the relationship between background characteristics and residential satisfaction of young households in unplanned neighbourhoods in Kano, Nigeria. Data was collected from 364 respondents using self-administered questionnaire from three unplanned neighbourhoods. Pearson's correlation analysis revealed age, household income, household size, total number of bedrooms and total number of rooms had positive significant relationship with residential satisfaction of young households in unplanned neighbourhood in the study area. However, there was no significant relationship between length of residence and residential satisfaction of the young households. Analysis of variance (ANOVA) showed that residential satisfaction differed between tenure status and house type of the respondent, while residential satisfaction did not differ between levels of education. Independent t-test revealed that there was no significant difference between employment status and residential satisfaction of the respondents. These relationships indicate that those who are older, higher income and bigger household size, with more room are more satisfied. It is recommended that policy makers and planning authorities should give more emphasis on the improvement of housing situations of young households and their income to enhance their residential satisfaction.